An Integrated Production System for a Single Installment Policy of Raw MaterialThis paper considers a manufacturing system which procures raw materials from suppliers and processes them to make a finished product. The problem is to determine an optimal pr - Omar, Mohd; Supadi, Siti Suzlin (Malaysian Journal of Science, 2008)
This paper considers a manufacturing system which procures raw materials from suppliers and processes them to make a finished product. The problem is to determine an optimal production size with a single installment of raw materials to satisfy a deterministic time-varying demand process by minimizing the total relevant cost. We developed a mathematical model for the problem and then compared the result with a lot-for-lot model with single installment and lot-for-lot model with multiple installments. From the optimality condition, we derived an optimal solution procedure for the proposed model. We present numerical examples for a discussion and comparison. Affiliation: